The spinning heart - Ryan, Donal 1977- (Doubleday Ireland, 2014)
"In the aftermath of Ireland's financial collapse, dangerous tensions surface in an Irish town. As violence flares, the characters face a battle between public persona and inner desires. Through a chorus of unique voices, each struggling to tell their own kind of truth, a single authentic tale unfolds."--Dust jacket
Novel
Keywords: City and town life / Ireland / Fiction; City and town life; Ireland / Fiction; Ireland; Irland; Fiktionale Darstellung